Ukraine: an Example of Limits of Balance and Asymmetric Reaction in the Maritime Trade Market - Primachev, Nicolas; Frasinyuk, Tatyana (Przegląd Wschodnioeuropejski, 2019)
This article deals with the principles of reaction of shipowners’ structures on the set of changes in the maritime trade market’s parameters. There are features of decision-making within the uncertain variability of the maritime trade market. Thus there are subsystems clearly realizing prioritizing strategies, and subsystems that choose the form of reaction to changes in the conditions of limited resources in the structure of the global maritime transport industry. Maintaining a balance, as the most effective condition of any market, plays a special role in maritime transport due to the high cost of fleet deadweight and the intensity of the crews’ work. Therefore, the clarity and timeliness of the response to external changes in traffic flows and carrying capacity of competing shipping companies becomes paramount.